KONSTRUKSI DAN EFEKTIVITAS KONSELING PRANIKAH DI KUA KECAMATAN GAYAM DALAM MENINGKATKAN KESIAPAN BERKELUARGA - Wawan Juandi; Riyan Hidayat (Maddah : Jurnal Komunikasi dan Konseling Islam, 2026)
The high challenges in modern household dynamics demand mature preparation for prospective bride and groom couples. The Office of Religious Affairs (KUA) of Gayam District, Sumenep Regency, implements premarital counseling as an instrument to mitigate the risks of unreadiness. This study aims to analyze the construction and implementation of premarital counseling at KUA Gayam District and its implications for the psychological and religious readiness of prospective couples. This study employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted by juxtaposing field findings with behavior change and marital readiness theories. The research findings indicate that the construction of premarital counseling at KUA Gayam has transformed from a mere administrative procedure into a value incubation process through three pillars: religious (theological foundation), psychological (character exploration), and relational (parental approach). The implementation of counseling utilizes a dialogic lecture method that effectively triggers behavioral changes from the contemplation stage toward collective commitment readiness. Premarital counseling at KUA Gayam is proven to be a strategic social laboratory in strengthening family resilience. The synergy between the internalization of religious values and the strengthening of interpersonal communication significantly contributes to the maturity of prospective couples in facing the complexities of married life.